Low cost joining of SS304-SS304 through microwave hybrid heating without filler-powder. (15th November 2019) - Bagha, Lucky; Sehgal, Shankar; Thakur, Amit; Kumar, Harmesh; Goyal, Deepam
Abstract: In this paper, a novel microwave joining technique for SS304-SS304 has been proposed, implemented and optimized, which does not require any filler-material at the joint interface. Absence of filler-powder drastically reduces the material cost of the joining process. The vertical cavity-type charcoal feeder has been used to concentrate heating effect around the joint region. Results of physical and mechanical characterization tests confirm the achievement of good homogeneity, hardness, tensile strength, and ductility in the joint region. Additionally, the process time has been optimized under geometric constraints on diameter and height of cavity. Optimization results show that the fastest joining process is achieved when cavity diameter and height are set to be 15 mm and 31.1 mm respectively.